Optimum plot size for banana trials - Nokoe, S.; Ortíz, R. (1998)
Bananas (Musa spp. AAA group) are an important food and a source of income for farmers in tropical countries. Black sigatoka (Mycosphaerella fijiensis Morelet), a fungal leaf spot disease, is the major production constraint worldwide. The replacement of most of the susceptible banana landraces requires the proper assessment of host plant response to black sigatoka and the determination of yield potential (per unit area and time) of the new selections. Although optimum plot sizes have been reported earlier for banana trials, the number of plants per plot was determined primarily by using a subjective visual assessment, based on the point of maximum curvature. This paper presents an objective method to determine optimum plot size using segmented models. Data on host response to black sigatoka, and growth and yield characteristics recorded in the plant crop and first ratoon on competing plants of the widely grown banana cv. Valery, provided the sample to illustrate the proposed method. With few exceptions, feasible solutions were obtained after <10 iterations. The approximate solutions suggested that nine to 33 plants per plot could be optimal for banana trials. The optimum number of plants per plot depended on the characteristic of interest and the production cycle. About 13 ± 1 plants may suffice to assess the host response to black sigatoka, whereas 16 ± 3 plants per plot are needed to evaluate growth characteristics and yield potential of cultivars. The optimum number of plants needed to assess the performance of genotypes had lower coefficients of variation in the plant crop than in the ratoon crop. Hence, the recommended optimum plot size consisted, on average, of 13 ±3 plants per plot for the plant crop, and 15 ±2 plants per plot for the ratoon crop. The suggested procedure to determine optimum plot sizes may prove useful for other crops.